Statistical study of geomagnetic field line resonances observed by CHAMP and on the ground. Issue 5 (3rd May 2013) - Heilig, B.; Sutcliffe, P. R.; Ndiitwani, D. C.; Collier, A. B.
Abstract : [1] Studies of single events showing the signatures of Pc3 pulsation field line resonances (FLRs) observed in magnetic field data by CHAMP above the E‐region ionosphere and at conjugate ground stations at L < 2 have previously been reported. Notable features of FLRs observed in these investigations were a Doppler shift in the satellite azimuthal component and a 90° rotation of the polarization ellipse between CHAMP and the ground. In this report, we extend the previous work by means of the first statistical investigation of the same features for a large number of events using CHAMP and ground magnetic field data. Our statistical study confirms the Doppler shifts to higher or lower frequencies relative to the ground FLR frequencies for equatorward or poleward passes of CHAMP over the ground station. Our statistical investigation shows the amount of rotation of the FLR polarization ellipses between the ionosphere and the ground to be 100° on average, rather than the theoretically predicted 90°. This is explained by the polarization ellipses on the ground being oriented close to N‐S irrespective of the orientation above the ionosphere, which is −13° on average. We find no evidence of ionospheric conductivity gradients associated with sunrise and sunset affecting the amount of rotation of the polarization ellipses as predicted by more recent theoretical advances. We are not able to provide conclusive evidence on the relationship between the polarization ellipse rotation and azimuthal wave number as predicted in recent numerical modeling. Key Points: This is the first statistical study on field line resonances observed at LEO. Our study confirms the Doppler shifts for passes of CHAMP over a ground station. Resonant widths were estimated from the observed Doppler shifts.